Highly porous polymer nanofibrous aerogels cross-linked via spontaneous inter-fiber stereocomplexation and their potential for capturing ultrafine airborne particles. (28th September 2019) - Ma, Xiu Yun Daphne; Ang, Jia Ming; Zhang, Youfang; Zeng, Zhihui; Zhao, Chenyang; Chen, Fenggui; Ng, Bing Feng; Wan, Man Pun; Wong, Shing-Chung; Li, Zibiao; He, Chaobin; Lu, Xuehong
Abstract: In this article, we design stable, highly porous PLLA/PDLA blend nanofibrous aerogels (NFAs) fabricated by cross-linking the electrospun nanofibers via spontaneous inter-fiber stereocomplexation, and the potential of the NFAs as an air filter for capturing ultrafine airborne particles. It is found that the extent of crosslinking can be easily controlled by adjusting the molecular weights of the polymers and their ratio. Compression tests reveal that the PLLA/PDLA blend NFAs exhibit significantly higher compressive resistance than their PLLA counterparts, demonstrating the effectiveness of the cross-linking. When combined with a layer of HEPA filter to form a composite filter, the NFAs show the potential to significantly improve the filtration efficiency for ultrafine particles with a slight increase in pressure drop. This is attributed predominantly to the high porosity of the NFAs, as well as the slip flow effect of nanofibers. The greater thickness of the highly porous NFAs leads to increased residence time of the ultrafine particles and hence enhances the probability of capturing particles through Brownian motion. This unique approach to spontaneously cross-linking electrospun nanofibers may also be applied to other stereocomplex systems or used for applications in other fields. Graphical abstract: Image 1 Highlights: PLLA/PDLA blend nanofibers are cross-linked by spontaneous stereocomplexation. Extent of crosslinking is related to the molecular weights and PLLA/PDLA ratio. PLLA/PDLA blend nanofibrous aerogels show greater compressive resistance. Highly-porous aerogel filters exhibit high PM0.1 efficiency and low pressure drop.